Gastrodiplomasi dan Identitas Nasional: Studi Thailand, Vietnam, dan Singapura - Ilham Surya Pratama; Roby Rakhmadi; Kevin Hansen Tamba (Terekam Jejak Publisher, 2024)
A country's cuisine is a fundamental component of its identity and culture because it captures the spirit of its customs, history, and values. Food can be readily communicated with people worldwide in an era of increased mobility, globalization, and technology. This has led to the growth of